NILAI-NILAI PENDIDIKAN AKHLAK DI DALAM KITAB AL-RISALATUL QUSYARIYAH - Abdul Rohman Nasution (Edu Global : Jurnal Pendidikan Islam, 2021)
Reality in people's lives proves that education is not able to produce quality output evenly. Evidenced by the still many crimes occur in the community, for example stealing, children against their parents, the rise of drug users, murder, adultery, gambling, brawl, sexual harassment, promiscuity, and many other crimes. Drug abuse has increased from time to time in Indonesia This study aims to determine the values ​​of moral education according to Imam Qusyairi in the book Ar Risalatul Qusyairiyah. This type of research is library research and qualitative descriptive approach. Research Results The values ​​of moral education contained in this book are sincere, repentant, trustworthy, patient, happy, glorifying teachers, friendship The application of moral education values ​​in learning both formal, non-formal, and informal is guiding students to have quality faith, piety and noble character.